2014
DOI: 10.12720/ijsps.3.1.14-18
|View full text |Cite
|
Sign up to set email alerts
|

An Image Retrieval Method Using Homogeneous Region and Relevance Feedback

Abstract: Relevance feedback and region based image retrieval are two effective ways to improve accuracy in content-based image retrieval. In this paper, we propose a content-based image retrieval method using relevance feedback and homogeneous region. By extracting a number of homogeneous color regions from the image and calculating the occurrence frequency of regions, we convert image feature vectors to weighted vectors. On the basis of the weighted vectors, we calculate the similarity between two weighted vectors and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…OrtegaBinderberger et al, 2004;D. Liu et al, 2009, Mattia Broilo et al, 2010Andre B et al, 2012;Hieu. V. V., Quynh.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…OrtegaBinderberger et al, 2004;D. Liu et al, 2009, Mattia Broilo et al, 2010Andre B et al, 2012;Hieu. V. V., Quynh.…”
Section: Introductionunclassified
“…As shown in Figure 1(a), the initial research which use this approach can found in [Smith, J.R et al, 1996;Ishikawa, Y et al, 1998;Porkaew, K. et al, 1999;D. Liu et al, 2009;Andre B et al, 2012;Hieu. V. V., Quynh N. H., 2014] represents a new query by a single point and adjusts the weights of feature components to find an optimal query point and distance function.…”
Section: Introductionmentioning
confidence: 99%